The effects of vildagliptin compared with metformin on vascular endothelial function and metabolic parameters: a randomized, controlled trial (Sapporo Athero-Incretin Study 3) - Naoyuki Kitao (Cardiovascular Diabetology, 2017)
Abstract Background Dipeptidyl peptidase-4 (DPP-4) inhibitors may have protective effects in the early stage of atherosclerosis in patients with type 2 diabetes, although similar effects in advanced atherosclerosis were not shown in recent randomized placebo-controlled studies. Therefore, we investigated the efficacy of DPP-4 inhibitor on endothelial function and glycemic metabolism compared with high-dose metformin. Methods In this multicenter, open-labeled, prospective, randomized, parallel-group comparison study, patients with type 2 diabetes treated with low-dose metformin (500–750 mg/day) were enrolled and randomly assigned to a vildagliptin, a DPP-4 inhibitor, add-on group (Vilda) or a double dose of metformin group (high Met) for 12 weeks. Flow-mediated dilation (FMD) and serum metabolic markers were assessed before and after treatment. In addition, glycemic control and metabolic parameters were also assessed. Results Ninety-seven subjects (aged 58.7 ± 11.0 years; body mass index, 25.9 ± 4.4 kg/m2; HbA1c, 7.3 ± 0.5%; FMD, 5.8 ± 2.6%) were enrolled. Eight subjects dropped out by the end of the study. There were no significant differences between the two groups in baseline characteristics. After 12 weeks, HbA1c was significantly improved in the Vilda group compared with the high Met group (− 0.80 ± 0.38% vs. − 0.40 ± 0.47%, respectively; p < 0.01). However, there were no significant differences in FMD (− 0.51 [− 1.08–0.06]% vs. − 0.58 [− 1.20–0.04]%). Although the apolipoprotein B/apolipoprotein A1 ratio was significantly reduced in the Vilda group compared with baseline (0.66–0.62; p < 0.01), the change did not differ significantly between the two groups (− 0.04 vs. 0.00; p = 0.27). Adiponectin levels were significantly increased in the Vilda group compared with the high Met group (0.75 μg/mL vs. 0.01 μg/mL; p < 0.01). Conclusions Regardless of glycemic improvement, combination therapy of vildagliptin and metformin did not affect endothelial function but may exert favorable effects on adipokine levels and lipid profile in patients with type 2 diabetes without advanced atherosclerosis.